2010
DOI: 10.1080/13603111003778429
|View full text |Cite
|
Sign up to set email alerts
|

Modelling inclusive practices in postgraduate tertiary education courses

Abstract: This paper is a teaching reflection. It gives an account of the delivery of two courses dealing with inclusive education. Both were delivered via external mode at the postgraduate level (i.e. distance education including web-based presentations and alternative resource delivery). While university education lecturers often talk about, and promote, Universal Design for Learning (UDL) and curriculum differentiation as the foundations of inclusive education, they do not appear to apply the relevant principle to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…A consistent finding indicates a broad knowledge of the theory and practices behind the philosophy of IE (Campbell, Gilmore, & Cuskelly, 2003;Sharma, Forlin, Loreman, & Earle, 2006), along with the legislation and government policy that surrounds and informs the practice (Ashman, 2010;Sharma et al, 2003), helps facilitate a positive attitude towards IE in pre-service teachers. Whilst the completion of a unit of study involving these concepts assists to foster a positive attitude (Lancaster & Bain, 2010;Sharma et al, 2008;Sosu, Mtika, & Colucci-Gray, 2010), the benefits have been found to be heavily dependent on the quality of education provided .…”
Section: Pre-service Teacher Training and Iementioning
confidence: 74%
“…A consistent finding indicates a broad knowledge of the theory and practices behind the philosophy of IE (Campbell, Gilmore, & Cuskelly, 2003;Sharma, Forlin, Loreman, & Earle, 2006), along with the legislation and government policy that surrounds and informs the practice (Ashman, 2010;Sharma et al, 2003), helps facilitate a positive attitude towards IE in pre-service teachers. Whilst the completion of a unit of study involving these concepts assists to foster a positive attitude (Lancaster & Bain, 2010;Sharma et al, 2008;Sosu, Mtika, & Colucci-Gray, 2010), the benefits have been found to be heavily dependent on the quality of education provided .…”
Section: Pre-service Teacher Training and Iementioning
confidence: 74%
“…This case study in new curriculum for a complex STEM subject found the student-centred learning of collaboration, computer-based analysis, and an open student choice of personal research interests, to be highly inclusive in the ways proposed by the literature reviewed (Tait, 2009;Ashman, 2010;Koppi et al, 2010), especially for gender (Wistedt, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…According to United Nations conventions, all governments are currently required to ensure the rights and equal opportunities of peoples with impairments through the collaborative efforts of policy makers, practitioners, people with impairments and their associations (Mji, MacLachlan, Melling-Williams & Gcaza, 2009:1). [1] As the role of teacher education is vital for HEIs to ensure equal opportunities for learners with diverse needs (Opertti, Brady & Duncombe, 2009:209; [2] Quality Assurance Agency (QAA), 2010:11 [3]), all university staff need extensive training in inclusive education (Sapon-Shevin, 2007:100). [4]) Especially, the Ethiopian Ministry of Education/MoE (2006:24, 25) [5] requires all teachers of students with VI to have a good understanding of the principles of inclusive education by incorporating introductory courses in special needs education in the regular teacher training program since 2006.…”
Section: Background and Statement Of The Problemmentioning
confidence: 99%